Quality of life and periodontal health. - Miranda Lins, Dario; Marinho Silva, João (Brazilian Journal of Implantology and Health Sciences, 2021)
Aim: This pilot study assessed the oral-health-related quality of life (OHRQoL) after long-term periodontal therapy and explored OHRQoL differences along the 2018 Classification of Periodontal Diseases. Methods: Sixty patients were examined before (T0) and after active periodontal therapy (APT/T1) and 32.0 ± 2.9 [range: 27–38] years of supportive periodontal therapy (SPT/T2). Periodontal diagnosis at T0 was assessed according to the 2018 Classification of Periodontal Diseases (stage 1/2/3/4: n = 1/3/44/13; grade n = A/B/C: 0/8/53). OHRQoL at T2 was measured using the Oral Health Impact Profile-G14 (OHIP-G14). Patients’ Eichner’s classification, accumulated tooth loss and treatment outcomes (SSO criteria) were assessed at T2. Generalized linear modelling (GLM) assessed associations between different factors and OHrQoL. Results: Mean OHIP-G14 sum score was 3.7 (SD 5.6). There was no statistically significant association between OHIP-G14 and gender, stage, SSO criteria and tooth loss. OHIP-G14 was significantly lower in older patients (−0.2[−0.3;0] per year, p = .008), non-smokers (−5.9[−9.9;-1.9] p = .003) and former smokers (−7.4[−11.6;- 3.2]; p < .001) versus current smokers, patients with Eichner class A1–B2 versus C2 (p < .05), sufficient adherence during SPT (−2.3[−4.6;-0.1], p = .044) versus insufficient ones. Patients with grade B (4.4[1.3;7.4]; p < .005) showed higher OHIP-G14 than those with grade C. Conclusion: A number of aspects, grounded in the initial diagnosis, the adherence to SPT, the resulting dentition, socio-demographic and behavioural covariates, were associated with good OHrQoL